High Order Thinking Skill dalam Pembentukan Karakter Siswa Sekolah Dasar di Era Industri 4.0 - Husni Mubarok (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2019)
The 2013 curriculum emphasizes the importance of High Order Thinking Skills and developing character values. It aims to balance intellectual ability and character in accordance with national education goals. This study aims to discuss a) the concept of High Order Thinking Skill, b) the concept of character building, and c) analysis of High Order Thinking Skills for character building elementary school students. The method used is library research with a qualitative approach. The research method is content analysis.The results of this study are 1) Higher Order Thinking Skill is a process of thinking critically, creatively, analytically to information and data in solving problems with cognitive, affective, and psychomotor skills that become a unity in the learning and teaching process. 2) Character is a way of thinking and behaving that characterizes each individual to live and work together. 3) The application of HOTS in the industrial era 4.0 using 4Cs Learning (critical thinking, communication, collaboration, and creativity) are four skills to foster character in elementary school students.